Development of Google Sites-based blended learning media on linier program material mathematics subjects - Suryati, Indah; Hadiwijaya, Slamet; Septiana, Tia (AIP conference proceedings, 2023)
Based on the 2018 PISA results, Indonesia’s average math score reached 379 with an OECD average score of 487. Students in Indonesia scored lower than the OECD average in reading, math, and science. Blended learning becomes a recommendation in an effort to improve learning. One of the blended learning media is a web-based learning media developed using Google Sites. The method used in this research is the Research and Development method. The data collection instruments used were observation, interview, and questionnaire. Questionnaires were employed to obtain media validity assessment data from material experts and media experts as well as obtain eligibility assessment data from teachers as practitioners of mathematics learning and students as targets of media use. The average score for the Linier Program of second-grade students at Madrasah Aliyah Negeri Wonogiri for the academic year 2021/2022 has not shown a significant increase in grades. Therefore, learning mathematics, especially linier programming, requires the appropriate media to explain the concept of linier programming clearly. Researchers create interactive learning media based on Google Sites. The media are entitled Prolin Sites which stands for Linier Program in Google Sites and has been tested on a small scale on 7 students of second grade and tested on a larger scale as many as 21 students of Madrasah Aliyah Negeri Wonogiri. The purpose of this research is to determine the validity and feasibility of using Google Sites-based interactive mathematics learning media on linier program material for second-grade class. Learning media Prolin Sites are valid and feasible to be used in learning activities. The media can inspire teachers and other researchers to innovate in developing learning media based on Google Sites.